IMPROVING THE SKILLS OF MIDWIVES IN OVERCOMING PREGNANCY DISCOMFORT WITH EARLY POSTPARTUM AND PREGNANCY EXERCISES - Panselina Widowati, Lorensia; Suci Dwi Aningsih, Baharika; Sri Artina Dewi, Ni Nyoman; Novitasari Suhaid, Dewi; Ida Pratiwi, Agustina; Leoni Irawan, Yetty; Kusumo Wardani, Dyah Woro Kartiko; Margaretha Manungkalit, Eviyani (LPPM Univ. Ibn Khaldun Bogor, 2023)
Pregnancy is a process that a woman looks forward to, but during pregnancy, there are various complaints that are felt due to physical and psychological changes and cause discomfort. Changes that occur due to changes in hormones and the psychology of pregnant women Increasing gestational age results in increasingly diverse complaints in pregnant women, especially in the third trimester. The complaints that are often experienced are back pain caused by excessive bending, walking without rest, and lifting weights. Midwives have an important role in improving the health of pregnant and postpartum women to overcome discomfort during pregnancy, childbirth, and the early postpartum period. This community service is carried out so that midwives can reduce discomfort for pregnant women, so they need to receive training in pregnancy and early postpartum exercises to improve their skills. There were 18 participants in the course, all of whom are currently employed as midwives for the Siloam Hospital Group. The course was considered successful after receiving an improving score from all participants.